Power Plant Performance Analysis on Variations of Generator Loading at Ombilin Coal Fired Steam Power Plant Unit 1 (2x100 MW) - Adytia Putra, Ryan; Nazir, Refdinal (LPPM Universitas Andalas, 2023)
Abstract— Steam Power Plants are classified as thermal plants that convert chemical energy in fuel into electrical energy. In an effort to increase the effectiveness of the work of the plant, there needs to be proper planning for its operations, this is important because it directly affects the operational costs incurred by the plant. This journal aims to determine the effect of changes in load or variations in generator loading on power plant performance, both efficiency, heat rate and production costs of electricity generation and to identify the magnitude of the decline in the thermal performance of the generator, as well as determine the causes and parts of the plant whose performance level decreases compared to optimal conditions. The method used to calculate the efficiency and heat rate is the “Direct Method”, namely by directly comparing the input energy with the electrical output produced. The data used in this study is the “Power Plant Performance Test” data. The results of this study get the most optimal conditions when loading 93.39 MW Net with efficiency 34.693%, heat rate 2475,445 kcal/kWh and electricity production costs 413,297 Rp/kWh. The conclusion of this study is that plant performance is getting better at high loads. Keywords: Thermal efficiency, Heat Rate, Electricity Production Cost, and Steam Power Plant